Experimental investigation of glass fiber-reinforced polymer composites during slot milling - Noha Naeim (Port Said Engineering Research Journal, 2023)
This paper presented the results of an experimental investigation on the machinability of glass fiber reinforced polymer (GFRP) composite materials during slot milling operations. A complete factorial design was used to perform the studies. The impact of milling parameters such as cutting speed, feeding rate, and inclination angles on material removal rate, machining time, tool wear, and surface finish (Ra) was studied using an analysis of variance. The results demonstrated that the feeding rate substantially influences the MRR with a p-value of 0.001314, spindle speed came in second with a p-value of 0.8896, while spindle speed and feeding rate were the two variables that had the greatest influence on machining time, with a p-value of 0.002604 for each, respectively. Additionally, feeding rate had the most impact on tool wear with a p-value of 0.0051793, followed by spindle speed with a p-value of 0.0012968. Furthermore, feeding rate, with a p-value of 0.0041408, was the factor that had the greatest impact on Ra, followed by spindle speed, with a p-value of 0.0024786.